Analysis of Factors that Influence the Use of Online Investment Applications (Ajaib) - Edward Adi; Sfenrianto Sfenrianto (Syntax Idea)
The purpose of this study is to analyze the factors that influence people who use the Ajaib mutual fund application. The proposed model considers factors from Technology Adoption Theory (TAM), which are implemented in this study to analyze how technology adoption impacts investments in online mutual funds, with Millennials being the focus of the primary research. This research is quantitative in nature and uses the survey method through the distribution of online questionnaires. Sampling using purposive sampling method. This study Used 5 internal variables and 3 external variables which are User Interface, Perceived Security and Perceived Risk. After collecting data from 400 respondents, it was found that there are several factors that positively influence the actual use of the online mutual fund application adoption system, User Interface, Perceived Security, Perceived Risk, Perceived Usefulness, Perceived Ease of Use, Attitude Towards Use, and Behavioral Intention off Use on the Ajaib application actual use of the system. This insight will be helpful for online mutual fund application developers to convert the traditional mutual fund into an online platform format.